2017
DOI: 10.20885/jeki.vol3.iss2.art3
|View full text |Cite
|
Sign up to set email alerts
|

Relevansi carbon emission disclosure dan karakteristik perusahaan pada perusahaan yang terdaftar di Jakarta Islamic Index

Abstract: This study aimed to analyze the influence of corporate's characteristics toward carbon emission disclosure and disclosure of carbon emission effect toward firm value. Companies characteristics variable are proxied by firm size, profitability and leverage. The sampling method is a company incorporated in the Jakarta Islamic Index (JII) which amounted of 34 companies. The data used in this study is the annual reports of each companies obtained through the Indonesia Stock Exchange and the hypotheses were tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
5
1
4
Order By: Relevance
“…The larger the size of a company, the greater the pressure on economic activity it will get. Contrary to the results of previous research, Irwhantoko and Basuki (2016) and Cahya (2017) found that there is no relationship between company size and disclosure of carbon emissions because not all large companies disclose carbon emissions. Healy and Palepu (2001) in their research found that the level of information asymmetry has a significant effect on environmental disclosure, this is because managers use voluntary disclosure as a tool to reduce misunderstandings related to company spending.…”
Section: Introductioncontrasting
confidence: 83%
“…The larger the size of a company, the greater the pressure on economic activity it will get. Contrary to the results of previous research, Irwhantoko and Basuki (2016) and Cahya (2017) found that there is no relationship between company size and disclosure of carbon emissions because not all large companies disclose carbon emissions. Healy and Palepu (2001) in their research found that the level of information asymmetry has a significant effect on environmental disclosure, this is because managers use voluntary disclosure as a tool to reduce misunderstandings related to company spending.…”
Section: Introductioncontrasting
confidence: 83%
“…This theory shows the relationship between stakeholders and the concept of legitimate, and it is understood that social responsibility disclosure has an impact on corporate reputation (Gunawan and Susilo, 2021). The company will act to protect the environment as desired by society (Cahya and Hanifah, 2017). Thus, legitimacy theory provides ideas for companies to take responsibility for the environment, so that the company can gain legitimacy from the community so that the company can maintain its existence.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ahmad and Hossain (2015), legitimacy theory is one of the theories underlying the incentives of entities that voluntarily disclose social and environmental responsibility reports. The company will act to protect the environment as desired by society (Cahya and Hanifah, 2017). Thus, legitimacy theory provides ideas for companies to take responsibility for the environment, so that the company can gain legitimacy from the community so that the company can maintain its existence.…”
Section: Legitimacy Theorymentioning
confidence: 99%
“…In contrast, large companies do not necessarily get maximum profits because large companies use greater operational costs. The firm size does not influence the disclosure of greenhouse gas emissions because large companies still believe that disclosure could be more effective and do not think it will negatively impact the future (Cahya, 2016). Companies also think that making disclosures will increase the company's burden because there is no awareness from company interns.…”
Section: Discussionmentioning
confidence: 99%